PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA PELAJARAN PKN DI SMA NEGERI 1 WATANSOPPENG - Hasnawi Haris; Fitriani B (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2018)
This study aims to determine: 1). Consideration teachers use cooperative learning model STAD on Civic Education in SMA Negeri 1 Watansoppeng; 2). How teachers implement cooperative learning model STAD on Civic Education in SMA Negeri 1 Watansoppeng; 3). Factors that can hinder and support the implementation of cooperative learning model STAD on Civic Education in SMA Negeri 1 Watansoppeng. This research is a qualitative descriptive study. Data obtained by the primary data obtained through direct foray into the field to interview and observation, and secondary data was obtained with an assessment of some of the literature related to the research. The data obtained and analyzed using qualitative descriptive analysis. The results showed that the consideration of teachers implement cooperative learning model STAD on Civic Education in SMA Negeri 1 Watansoppeng are: 1) Make it easier for teachers to know the type of cooperative learning with the simple concept of work; 2) To train students to work together; 3) To train students to interact and communicate well, train students to actively discuss; 4) To train students to avoid individual properties and to be selfish; 5) The teacher must adjust the Basic Competency (KD) in accordance with the model type STAD cooperative learning that lesson material contains many aspects of values, knowledge and skills. As for how teachers use cooperative learning model STAD was in accordance with the steps of cooperative learning model STAD. While the factors inhibiting and supporting the implementation of cooperative learning model STAD, inhibiting factors, namely: 1) Students do not pay attention to the teacher while teaching; 2) Students are more often silent during the discussion; 3) Students are spending less time as efficiently as possible; 4) The number of students in a class; 5) The classroom atmosphere is hot. The supporting factors, namely: 1) Students are happy using cooperative learning model type STAD; 2) Students are taught how to be responsible with lessons task completion; 3) The creation of an intimate relationship in the classroom between teachers and students as well as students with students; 4) Equipped with facilities and infrastructure that support learning and; 5) Teachers who are already capable of using cooperative learning model STAD.